Implementation of Workflow Management System on E-Learning Platform for The Effectiveness of Distance Learning - Yuthsi Aprilinda; Agus Sukoco; Ahmad Cucus (International Conference on Engineering and Technology Development (ICETD), 2014)
This sresearch aims to develop an e-learning as a kind of learning systems using Internet media, e-learning using information technology as a tool that can be available wherever it is needed. One of the e-learning development techniques to become more efficient is by applying workflow management system (WFMS) in developing e-learning. Because WFMS focuses on business processes, it is concerned with the automation of procedures so that the information and tasks assigned to run a more efficient and coordinatedapplication-based e-Learning open source workflow can be applied in all educational institutions, because e-learning can follow the learning procedures that exist in the educational institutions.